Analysis of Distributive, Procedural and Interactional Service Recovery and Its Impact on Customer Satisfaction of J&T Courier Services in Pekanbaru City - Nuryuni Nabila; Annisa Meliana; Fharisa Nabila Rizvi; Ronal Kurniawan; Okta Rizal Karsih (Science, Technology, and Education Care, 2026)
The courier industry in Indonesia has experienced significant growth in recent years, driven by the rapid expansion of e-commerce and increased online shopping activity. This study is based on the fact that many customer complaints regarding J&T services, such as late deliveries, damaged goods, and difficulties communicating with couriers, remain, despite J&T being one of the courier service companies with the highest market share in Indonesia. This study aims to analyze the effects of service recovery on distributive, procedural, and interactional justice. The study was conducted from August to September 2025. The method used was quantitative, with a descriptive approach. Data were collected through questionnaires administered to 100 residents of Pekanbaru City who had used J&T services and experienced delivery-related complaints. The analysis technique used was multiple linear regression in SPSS. The results show that, both partially and simultaneously, distributive, procedural, and interactional service recovery have a positive and significant influence on customer satisfaction. This implies that the better the company handles complaints using an appropriate justice approach, the higher the customer satisfaction